Transposon mutagenesis in Desulfovibrio desulfuricans: development of a random mutagenesis tool from Tn7. - Wall, J D (1996)
The transposons Tn5, Tn7, Tn9, and Tn10 or their derivatives have been examined for transposition in the sulfate-reducing bacterium Desulfovibrio desulfuricans G20. Tn7 inserted with a frequency of 10(-4) to 10(-3) into a unique attachment site that shows strong homology with those sites identified in other gram-negative bacteria. Inactivation of the tnsD gene in Tn7, encoding the function directing insertion into the unique site, yielded a derivative that transposed essentially randomly with a frequency of ca. 10(-6) per donor. Derivatives of Tn5, but not wild-type Tn5, were also found to undergo random transposition at a similar frequency. No evidence was obtained for transposition of Tn9 or Tn10.